Valorization potential of coffee grounds waste as a renewable pore-forming agent to produce low-cost porous ceramic support (Research, Society and Development, 2023)
Every day expressive amounts of coffee grounds waste generated during making the coffee beverage are produced worldwide. The aim of this work was to investigate the valorization potential of the coffee grounds waste as an alternative pore-forming agent to produce porous kaolin-based ceramic supports. For this purpose, kaolin-based ceramic support formulations containing up to 40 mass % of coffee grounds waste were pressed and fired at temperatures ranging from 1000 to 1200 ºC. The sintering behavior and technical properties (linear shrinkage, mass loss, apparent density, mechanical strength, and apparent porosity) have been investigated. The microstructural evolution has been accompanied by scanning electron microscopy (SEM) and 3D-confocal microscopy. The obtained results demonstrated that the coffee grounds waste could serve as a very effective pore-forming agent to produce kaolin-based ceramic support with highly porous structures. Such ceramic supports incorporated with coffee grounds waste exhibited values of apparent porosity within the range of 41.87 % to 70.96 %. This results suggests that the coffee grounds waste, in the range of 10 - 40 mass %, could be a highly promising renewable porogenic material to be valorized to produce low-cost kaolin-based ceramic support with good porosity properties. This new approach could be an innovative alternative for the sustainable use of coffee grounds waste.